Firewall Design Using Access Control List Method As Data Filtering - Niar Adisty Putra; Verry Riyanto; Ganda Wijaya; Nuraeni Herlinawati (Jurnal Mantik, 2021)
The need for real-time information is very important, to get it quickly and even in real time it must be supported by a fast and stable internet network connection. In addition, it must also be able to protect the network connection from all kinds of threats that can interfere with the connectivity of the connection. In implementing the firewall within the company, the concern is the device used, because the implementation of the firewall on each device is different. Utilization of this firewall is used to filter data packets that will enter the network, using the ACL feature. By using ACL data filtering can be done or as a site blocker that is considered unnecessary to be accessed by all clients on the local network. In addition, as security in the local network, the logical division of network groups can be applied using VLANs, the application of VLANs is found on Catalist Switches or Multilayer Switches. As a security for the physical path of the VLAN connection, a special physical connection path is given to important network devices, so that if there is a down or disconnected physical path, it does not interfere with other VLAN connections